The Validity Of Divorce Judgments By The Court For Catholic Couples According To Canon Law - Emia Regita; Sonny Dewi Judiasih; Bambang Daru Nugroho (Eduvest - Journal of Universal Studies, 2024)
This research discusses the validity of divorce judgments issued by civil courts against Catholic couples from the perspective of Canon Law. Canon Law itself, as the internal legal system of the Catholic Church, does not recognize divorce as a means to end a valid marriage. Marriage is considered sacred and indissoluble. Although civil courts have jurisdiction to issue divorce judgments according to state law, this research examines how such judgments are viewed from the perspective of Canon Law and their impact on the religious status of divorced couples. Through analysis, this research finds that divorce judgments by civil courts do not alter the marital status in the context of the Catholic Church, which still considers the marriage valid and binding. This finding highlights the legal dualism between state law and Canon Law and its practical implications for Catholic individuals facing divorce. This research recommends the need for a deeper understanding and sensitive handling of divorce cases involving Catholic couples to avoid legal and religious conflicts.